2021
DOI: 10.1186/s12913-021-07069-w
|View full text |Cite|
|
Sign up to set email alerts
|

Does integrated medical insurance system alleviate the difficulty of using cross-region health care for the Migrant Parents in China-- evidence from the China migrants dynamic survey

Abstract: Background Many internal migrants during the urbanization process in China are Migrant Parents, the aging group who move to urban areas to support their family involuntarily. They are more vulnerable economically and physically than the younger migrants. However, the fragmentation of rural and urban health insurance schemes divided by “hukou” household registration system limit migrant’s access to healthcare services in their resident location. Some counties have started to consolidate the Urba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…Referring to enabling resources, characteristics of medical insurance are associated with the availability of the insurance at the selected destinations and thus are related to IMs' HSU. For example, medical insurance type (14,100,145) and place of insurance enrollment (14,17,50,56,105) were found to be associated with IMs' HSU. These features would determine the level of insurance compensation and flexibility for IMs to transfer their medical insurance between hometowns and destinations (16,17).…”
Section: Ims-specific Factorsmentioning
confidence: 99%
“…Referring to enabling resources, characteristics of medical insurance are associated with the availability of the insurance at the selected destinations and thus are related to IMs' HSU. For example, medical insurance type (14,100,145) and place of insurance enrollment (14,17,50,56,105) were found to be associated with IMs' HSU. These features would determine the level of insurance compensation and flexibility for IMs to transfer their medical insurance between hometowns and destinations (16,17).…”
Section: Ims-specific Factorsmentioning
confidence: 99%
“…For example, Ren (2022) found that residents' health improved signi cantly after switching from low-grade to high-grade health insurance based on the urban-rural health insurance coordination pilot in Taicang and Yixing cities. However, Ma (2021) found, based on nationwide survey data, that although the policy of integrating urban and rural residents' health insurance signi cantly improves residents' health, it promotes health inequality.…”
Section: I Literature Review (I) Impact Of Health Insurance Coordinat...mentioning
confidence: 99%
“…This means that urban and rural residents are no longer restricted by geography and status and can enjoy uniform medical insurance payments and participation. After the integration of basic medical insurance, rural residents have equitable access to better medical services and greater protection ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%